Legal Efforts in Improving Children's Religious Education After Parental Divorce in Manado, Indonesia - Bukido, Rosdalina (The Center for Gender and Children Studies, the Institute for Research and Communing Service, State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2024)
This study describes the phenomenon of religious education that is felt by children after the child’s parents’ divorce. We conducted this research in Manado City. The researcher identified the children’s personality and how the child’s religious personality (morals) was. Researchers also conducted interviews with religious teachers and recitation teachers to understand the process of accepting religious teachings of these children. We analyzed subsequent studies through reduction, assessment, and drawing conclusions. The results obtained are that children do not get a good education, lack of motivation, enthusiasm for learning, decreased comprehension, do not try himself, are not disciplined. And the impact of divorce on children’s religious education is that children are lazy to recite the Koran, lazy to pray, polite to others and lazy to perform other obligatory worship. In Islam, parents are the first educators for children. Both from the mother’s and father’s sides. Each has a portion. A husband as well as a father has a big duty and responsibility, namely to prohibit good values for the child and for the wife, understand them, advise them and give love. As much as possible, maintain a husband-and-wife relationship so that it remains harmonious and away from conflict so that divorce does not occur. Because cases of divorce of parents greatly impact the physical, psychological and religious education of children.